Comparative study of various Watermarking Techniques - Prithesh S, Dr. M. Pradeepa (International Journal of Advanced Science and Technology, 2020)
In the present era, technology has developed enormously with respect to time and it’s still growing. Around 2.5 quintillion bytes of data are generated every single day and its value just keeps increasing. But on the other hand the need to protect data has also up surged due to security requirements. In this paper we discuss about various watermarking techniques that have been developed at different domains for the same reason and compare them. We focus mainly on digital data such as images and how to preserve its authenticity as well as detect unauthorized tampering using watermarking techniques. At the later part of the paper i have proposed and implemented a basic watermarking technique and discussed the same.